AN ANALYSIS OF EMPLOYMENT POTENTIALS OF COTTAGE, MICRO AND SMALL SCALE ENTERPRISES IN JIGAWA STATE OF NIGERIA - Yusuf, Muhammad Muazu; Saidu, Bello Malam; Ahmed, Bello Abba (European Scientific Journal, ESJ, 2015)
This paper examines employment potentials of Cottage, Micro and Small Scale Enterprises (CMSSEs) in Jigawa State, Nigeria. The data was obtained from a survey of 300 enterprises randomly selected from three local government areas of the state. Consequently, descriptive statistics and multiple regression were employed for the analysis. The result revealed that the explanatory variables that were found to be significant in explaining the employment potentials of the enterprises are; level of education, experience of the entrepreneurs, size of the enterprise, government support, gender and access to finance. Finally, the study recommends among others that government should improve its financial support to CMSSEs so that they could create more employment opportunities for millions of Nigerians.